Sustainability & Circular Economy in Manufacturing Supply Chains: Prioritizing Low-Carbon Production, Scope 3 Emissions, and Circular Models for ESG Compliance - Anumula, Sathish; Krishnapillai, Vijaykumar; Rai, Dileep Kumar; Bhattacharya, Shuvdeep; Nagella, Prasad (International Journal of Supply Chain and Logistics, 2025)
Purpose: Manufacturers across sectors are now trying to build sustainability and circular economy ideas into their supply chains. This is a move to meet their social and governance responsibilities and to keep up with the growing number of rules that aim to encourage sustainable practices. This project brings together a lot of progress in areas like reducing carbon in production, managing emissions making sure supplies are sourced responsibly saving energy and creating new circular systems for getting materials from one place to another. All these things are Working towards the goal; making the future a more sustainable place Methodology: The study starts with a look, at what’s been written on the subject and this foundation brings to light the key factors that are driving change and the main hurdles organizations are facing It also shows a spotlight on what works and presents a plan for putting sustainable practices into action, across different industries Findings: When you look at the results of this research it's clear that digital innovation, collaboration, between sectors and strong policy support are crucial for overcoming obstacles and helping businesses build supply chains that can last. What’s really needed for a shift to supply chains is a broad approach that brings together the latest technology and cooperation, between stakeholders to make a real difference. This way companies can create supply chains that're resilient and adaptable and able to withstand challenges over time. By taking this approach businesses can set themselves up for long-term success Unique Contribution to Theory, Policy and Practice: This research addresses the increasing demand for manufacturers to adopt sustainable practices and meet evolving Environmental, Social, and Governance (ESG) standards. The project synthesizes existing literature to highlight key drivers, challenges, and best practices in integrating sustainability into manufacturing supply chains. Digital innovation, cross-sector collaboration, and robust policy support are identified as crucial elements for building resilient and adaptable supply chains. Ultimately, a comprehensive approach that combines technological advancements with stakeholder cooperation is essential for achieving long-term success in sustainable manufacturing.